2019
DOI: 10.3390/atmos11010043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Particulate Matter Exposure on the Inflammatory Airway Response of Street Runners and Sedentary People

Abstract: Physical exercise promotes many health benefits. However, its effects are not well known in a polluted environment. Thus, this study aimed to compare upper airway inflammatory responses between street runners and sedentary individuals. Twenty-eight volunteers were recruited: runners (n = 14) and sedentary individuals (n = 14), who lived and worked in the same metropolitan area of São Paulo, Brazil. Particulate matter (PM) levels were monitored ten weeks before winter (low PM levels) and ten weeks after the beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Nowadays, air pollution is a major issue and the negative health effects of pollutants have been shown repeatedly [ 11 – 13 ]. This is also true for elite athletes, who perform intensive outdoor activities [ 14 – 16 ]. The positive effects of moderate-intensity exercise on health are widely recognised, resulting in a massive increase of running events for non-elite athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, air pollution is a major issue and the negative health effects of pollutants have been shown repeatedly [ 11 – 13 ]. This is also true for elite athletes, who perform intensive outdoor activities [ 14 – 16 ]. The positive effects of moderate-intensity exercise on health are widely recognised, resulting in a massive increase of running events for non-elite athletes.…”
Section: Introductionmentioning
confidence: 99%
“…In asthmatics, Pietropaoli et al [70] found increased macrophages in induced sputum when they performed two hours of intermittent exercise in an environment with ultrafine particulate matter (10 µg/m 3 ), unlike healthy subjects (10, 25, and 50 µg/m 3 ). A recent study highlighted the effect of outdoor endurance training as an immune protection factor against exposure to particulate matter by controlling lung inflammation in this group, but not in exposed sedentary subjects [71]. This reinforces the importance of controlling air quality, the type of exercise, and the level of physical condition in order to take advantage of its benefits and thus avoid the deleterious effects of pollution.…”
Section: Lung Inflammation and Oxidative Stress Due To Exercise In Polluted Airmentioning
confidence: 63%
“…Another limitation of this study is associated to the absence of assessments concerning to the pulmonary inflammatory condition of the volunteers both before and immediately after the race. In this way, it has been demonstrated that the evaluation of fractional exhaled nitric oxide (FeNO), a remarkable biomarker presenting increased levels in association with pulmonary inflammation, can be useful for monitoring pulmonary inflammatory status in different situations [54][55][56], including in the context of running [46,57]. Other points that deserve to be mentioned are related to the inclusion of only men in this study, the age of the participants, and also, to the environmental conditions present during the marathon event [58].…”
Section: Discussionmentioning
confidence: 99%